1999
DOI: 10.1046/j.1365-8711.1999.02481.x
|View full text |Cite
|
Sign up to set email alerts
|

The mass of X-ray Nova Scorpii 1994 (=GRO J1655-40)

Abstract: We have obtained high‐ and intermediate‐resolution optical spectra of the black hole candidate Nova Scorpii 1994 in 1998 May/June, when the source was in complete (X‐ray) quiescence. We measure the radial velocity curve of the secondary star and obtain a semi‐amplitude of K2=215.5 ± 2.4 km s‐1, which is 6 per cent lower than the only previously determined value. This new value for K2 thus reduces the binary mass function to f(M) = 2.73 ± 0.09 M⊙. Using only the high‐resolution spectra, we constrain the rotatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
123
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(137 citation statements)
references
References 21 publications
10
123
4
Order By: Relevance
“…The type A QPO peaks at 12 and 276 Hz appear to be consistent with a black hole mass of 8.9 M and a spin parameter of a=M ¼ 0:35, quite similar to the values used throughout much of this paper. For the black hole binary GRO J1655À40, we can fit the QPOs at 18 and 450 Hz with a mass of 5.1 M and a spin of a=M ¼ 0:28, slightly less than the published mass range of 5.5-7.9 M (Shahbaz et al 1999). If we relax the requirement of matching the LFQPOs and fit only the HFQPOs with a 1:3 coordinate frequency commensurability, there remains a one-dimensional degeneracy in the mass-spin parameter space.…”
Section: Noncircular Orbitsmentioning
confidence: 89%
“…The type A QPO peaks at 12 and 276 Hz appear to be consistent with a black hole mass of 8.9 M and a spin parameter of a=M ¼ 0:35, quite similar to the values used throughout much of this paper. For the black hole binary GRO J1655À40, we can fit the QPOs at 18 and 450 Hz with a mass of 5.1 M and a spin of a=M ¼ 0:28, slightly less than the published mass range of 5.5-7.9 M (Shahbaz et al 1999). If we relax the requirement of matching the LFQPOs and fit only the HFQPOs with a 1:3 coordinate frequency commensurability, there remains a one-dimensional degeneracy in the mass-spin parameter space.…”
Section: Noncircular Orbitsmentioning
confidence: 89%
“…As noticed from the bottom panel of Figure 1, the ratio between the X-ray and B-band fluxes marks the minimal value at around the Chandra observation after the hard-to-soft transition at ∼MJD 53440. We note that, among the 5 OIR bands, the Bband flux should have the least fractional contribution of the blackbody emission from the companion (an F6-III-type star with a temperature of »6300 K; Shahbaz et al 1999) and is dominated by the irradiated disk emission from the outer disk (see Section 3 for more details).…”
Section: Long-term Trends In Optical Near-infrared and X-ray Propermentioning
confidence: 99%
“…The OIR fluxes also include the blackbody emission from the companion star, for which we use the bbodyrad model. Throughout the SED analysis, we fixed the temperature and radius of the companion star to 6300 K and 5.0 ☉ R , respectively, and the BH mass at 6.3 ☉ M , following the previous estimation by Shahbaz et al (1999) and Greene et al (2001). The interstellar X-ray absorption is taken into account by multiplying the tbabs model (Wilms et al 2000).…”
Section: Model Setupmentioning
confidence: 99%
“…If we know K 2 and v rot sin i, then using equations (1) and (2) we may calculate q. The mass function of the companion star, derived from Kepler's Third Law, is given by Shahbaz et al 1999 where P is the orbital period of the binary and can be found from the radial velocity curve of the companion. Optical light curves can also be used to measure P. Together with K 2 , i and q, M 1 can then be evaluated from equation (3) and M 2 is found via q.…”
Section: Measuring the Mass Of The Compact Object From Companion Starmentioning
confidence: 99%
“…The overabundances of the alpha elements may be due to the supernova explosion that created the compact object; it is difficult to see how such abundances can be produced in the F star. Orosz & Bailyn (1997) and Shahbaz et al (1999) did not attempt to derive the metallicity. The rotational velocity has been measured by Shahbaz et al (1999) using spectra of real stars that span the spectral type and luminosity class of the companion star.…”
Section: The Companion Star In Gro J1655-40mentioning
confidence: 99%